ANALISIS PROSEDUR PENERJEMAHAN KATA DAN UNGKAPAN BERMUATAN BUDAYA DALAM NOVEL TWILIGHT DAN TERJEMAHANNYA - Natalia, Desie (Jurnal Penerjemahan, 2014)
This article tries to describe translation procedures applied by a translator -Lily Devita Sari-- in transferring American cultural words and expressions from English into Indonesian. By using Stephenie Meyer's novel Twilight and its Indonesian translation as the source of data, the writer applies a qualitative descriptive method to describe translation procedures used by the translator in transferring those cultural words and expressions. The result of the study proves that there are, at least, ten translation procedures applied by Lily Devita Sari, namely tranf erence, naturalisation, cultural equivalent, functional equivalent, through-translation, shift or transposition, recognized translation, reduction, expansion, and additions.